THE USE OF DEIXIS IN GLADIATOR MOVIE MANUSCRIPT - Hasanah, Chuswatul; Laila, Malikatul; Prasetyarini, Aryati (Universitas Muhammadiyah Surakarta, 2006)
This study is about the forms and references of deixis udes in